Electromagnetic properties of possible triple-charm molecular hexaquarks - Chen-Ke Zhang; Fu-Lai Wang; Si-Qiang Luo; Xiang Liu (European Physical Journal C: Particles and Fields)
Abstract In this study, we investigate the radiative transitions of predicted triple-charm molecular hexaquarks, which play a significant role in understanding their overall spectroscopic properties. As experimentally measurable quantities, the radiative decay widths provide insights into the internal structures of these triple-charm molecular hexaquarks. Additionally, we calculate their corresponding magnetic moments, which, together with the radiative decay widths, offer a comprehensive picture of the electromagnetic properties of these exotic states. This information is valuable for guiding future experimental searches and advancing our understanding of these unique hadronic systems.